Analisis Manajemen Pembelajaran Teaching Factory pada Kompetensi Keahlian Tata Busana untuk Menumbuhkan Sikap Kewirausahaan Peserta Didik di SMKN 2 Godean Sleman Yogyakarta - FAIZAH FAIZAH; Sutrisna Wibawa (Universitas Sarjanawiyata Tamansiswa, 2023)
The research objectives include: (1) analyzing the management of Teaching Factory learning in Cosmetology Expertise Competency to foster the entrepreneurial spirit of Fashion students which includes planning, organizing, implementing and evaluating functions, (2) analyzing the supporting and inhibiting factors of teaching factory learning in cosmetology expertise competency, (3) analyzing teaching factory learning solutions in cosmetology expertise competency at SMKN 2 Godean. This research is a qualitative research with data collection techniques including observation, interviews, and documentation. The informants of this research are the principal, vice principal of curriculum and public relations, special work exchange, head of the fashion craft program, teachers and students. Data analysis was conducted using the Miles and Huberman model, including: data reduction, data display and drawing conclusions. The research location is SMKN2 Godean with the address Jl. Jae Sumantoro, Sidoagung, Sleman, Yogyakarta. The results showed that the analysis of teaching factory learning management in the competence of fashion craftsmanship to foster entrepreneurial attitudes of students at SMKN 2 Godean Sleman Yogyakarta, can be seen in: (1) the management of teaching factory learning in the competence of fashion craftsmanship is seen in the planning that has been done well, the organization of learning is listed in the lesson plan document is implemented well can foster the entrepreneurial spirit of students, the implementation is in accordance with DUDI standards, the evaluation of teaching factory learning reinforcement analysis needs follow-up, and (2) supporting factors in teaching factory learning facilities and infrastructure that meet industry standards and competent teachers, The inhibiting factor is that there is no special building for the implementation of teaching factory learning so that in its current implementation it uses a semi-block schedule, the solution in dealing with obstacles is that in the future the school plans to build a new building for teaching factory learning.